Termite Prevention and Control - Faith Oi; James Davis; Julie McConnell; Judy Corbus; Nelly Nelson; Michelle Atkinson (EDIS)
This 16-page guide written by F. M. Oi, J. Davis, J. McConnell, J. Corbus, N. Nelson, and M. Atkinson and published by the UF/IFAS Entomology and Nematology Department is intended to help homeowners make informed choices about the best termite protection for their homes. https://edis.ifas.ufl.edu/in1277